A Deep Learning Based Method for Detecting Covid-19 from Colorized CT Images - Güngör, Semiha; Kaya, Mehmet; Alhajj, Reda (Ali KARCI, 2021)
A new coronavirus disease Covid-19 has been recorded in Wuhan, China since late December 2019 and later became a worldwide pandemic. It can result in death as a result of covid-19's damage to the alveoli and progressive respiratory failure. Although transcription polymerase chain reaction (RT-PCR) is the gold standard used for clinical diagnosis, tests can produce false negatives. In addition, in the event of a pandemic, the lack of RT-PCR testing resources may delay diagnosis and treatment. Under these circumstances, Computed Tomography (CT) scans have become a valuable tool for both early diagnosis and prognosis of Covid-19 patients. Recently, many studies developed with deep learning techniques have been proposed to facilitate the diagnosis of Covid-19 in CT scans and to assist healthcare professionals. This paper focuses on distinguishing Covid-19 from non-Covid-19 cases using DenseNet121, one of the deep learning techniques, with the CT dataset colored using the DeOldify library. At the end of our study, an accuracy of 0.98 was obtained.

Aralık 2019'un sonlarından bu yana Çin'in Wuhan kentinde yeni bir koronavirüs hastalığı Covid-19 kaydedildi ve daha sonra dünya çapında pandemik hale geldi. Covid-19’un, alveollerde bıraktığı hasar ve ilerleyen solunum yetmezliğinin bir sonucu olarak ölümle sonuçlanabilir. Klinik tanı için kullanılan transkripsiyon polimeraz zincir reaksiyonu (RT-PCR) altın standart olmasına rağmen testler yanlış negatifler üretebilir. Ayrıca pandemik durumda RT-PCR test kaynaklarının yetersizliği, tanıyı ve tedaviyi de geciktirebilir. Bu koşullar altında göğüs BT görüntülemesi, Covid-19 hastalarının hem tanı hem de prognozu için değerli bir araç haline gelmiştir. Yakın zamanda BT taramalarında Covid-19 tanısını kolaylaştırmak ve sağlık çalışanlarına yardımcı olmak için derin öğrenme teknikleriyle geliştirilmiş birçok çalışma önerilmiştir. Bu makale, DeOldify kütüphanesini kullanarak renklendirilen BT veri seti ile derin öğrenme tekniklerinden DenseNet121’i kullanarak Covid-19'u, Covid-19 olmayan vakalardan ayırt etmeye odaklanmaktadır. Çalışmamızın sonunda %98’lik doğruluk elde edilmiştir.
Renklendirilmiş BT Görüntülerinden Covid-19 Tespiti İçin Derin Öğrenmeye Dayalı Bir Yöntem
Keywords: Artificial Intelligence; Yapay Zeka